THE GREEKS OF GEORGIA: IGRATION AND SOCIOECONOMIC PROBLEMS - KOMAKHIA, Mamuka (CENTRAL ASIA AND THE CAUCASUS, 2005)
Greeks first came to western Georgia in the 8th-7th centuries B.C., yet the ancestors of most of the Greeks now living in the country came in the 19th and 20th centuries. Today, the once large diaspora (which comprised a significant part of Georgia’s population) has shrunk to several thousand people.The first wave of Greeks from Asia Minor (the Anatolian Greeks) was generated by Czar Irakly II’s economic projects implemented in the 1770s and the policies of the regional countries. Under the Kuchuk-Kaynardji Peace Treaty of 1774 between Russia and Turkey, the Russian Empire acquired a protectorate over the Greeks; this was followed by Greek migration to Russia. It was at the same time that Irakly II invited Greek artisans from the Erzurum and Kars regions to work at the newly opened silver and copper plants in Akhtal and Alaverdi. (About 800 Greeks with families moved to Georgia from the industrial centers of Asia Minor.)In fact, Russia deliberately created a Christian area in Georgia (where Armenians lived side-by-side with Georgians) which bordered on the Islamic world; this was further promoted by the resettlement of Greek refugees who came in great numbers, especially in the 19th century. Under the Adrianople Peace Treaty which put an end to the Russo-Turkish war of 1828-1829 Russia was expected to remove its troops from the Erzurum vilayet, a move which would have left the local Greeks who had been on the Russian side during the war unprotected. At General Paskevich’s request, Nicholas I allowed the Greeks to settle in Georgia. They came mainly to the Borchala uezd, which had been completely ruined by Turkish and Daghestani inroads. By 1830, about 18 Greek settlements had appeared in the Tsalka District. Simultaneously, Greeks from the northwestern vilayets of Turkey started moving to the Dmanisi District; they replaced the local Georgian geographic names with the names of the villages they left behind in Turkey. This part of the country still abounds in Turkish geographical names, even though over time some of the villages restored their old Georgian names. In the 1830s, Greeks moved to Samtskhe: 200 Greek families settled in the villages of Tsikhisdjvari (Borzhomi District) and Mikeltsminda (Akhaltsikhe District) depopulated by the Muslim incursions. The favorable living conditions made it much easier to strike root there than in the Tsalka District.